IMPLEMENTASI UNDANG-UNDANG NO 14 TAHUN 2008 TENTANG KETERBUKAAN INFORMASI PUBLIK OLEH PEJABAT PENGELOLA INFORMASI DAN DOKUMENTASI (PPID) KEMKOMINFO - Diliana Ade Pembayun; Aryo Bimo Oktafianto; Syafiq Basri Assegaff (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2019)
This research discusses about law No. 14 year 2008, the openness of public information implemented by the officers of the information and documentation Officer (PPID) Kemkominfo. The Act on public information disclosure aims to improve the management, service of information, and encourage public participation in the conduct of the State so as to realize the system of good governance. The purpose of this research is to describe how the Official information and documentation Manager (PPID) of the Ministry of communication and Informatics of carrying out the implementation of law No. 14 year 2008 about the openness of public information. The method used in this research is descriptive in nature with qualitative data collection techniques in the form of interviews with the informant Acting Manager of information and documentation. Data analysis techniques using models, Miles and Huberman that consists of data collection, data reduction, data display and verification, and assertion inference. Examination technique benefiting using triangulation of sources. The results of this research show the implementation ACT KIP done with through the six steps, namely: designating the PPID, build and make the system functional officials, pointing to information (public relations, archives, computer), providing information in the form (text, video, sound, infographics), providing information services in the form of front desk and website, as well as compiling daily, monthly and annual reports.